Wide-Angle Circular Polarization Converter Based on a Metasurface of Z-Shaped Unit Cells - Wang, Mingjun; Zhai, Zhizhu (Frontiers in Physics, 2020)
Since it’s designable, metasurface was widely used in various fields, especially the design of polarization converters. However, most of the polarization converters currently designed can only work under normal incidence or small angle incidence, which hugely limits the application of the device. In this paper, a chiral metasurface based on the z-shaped unit cell which can manipulate circular polarization wave is proposed. The simulation result shows that this converter can maintain the polarization state of circular polarization after reflection from 8.18 to 13.988GHz with a polarization conversion ratio more than 90%. Moreover, the structure is insensitive to incidence angle，which can keep a stable performance both for left-handed circularly polarized wave and right-handed circularly polarized waves as the incident angle increase to 75°. The proposed metasurface with simple structure, angular stability can be used in communication and polarization manipulating devices.